Portuguese Africa : a guide to official publications - Gibson, Mary Jane (General Reference and Bibliography Division, Reference Department, Library of Congress, 1967)
"This guide covers as comprehensively as possible the documents of Portuguese Africa from 1850 to 1964. It lists publications of the governments of Angola, the Cape Verde Islands, Mozambique, Portuguese Guinea, and the São Thomé e Principe Islands and also of Portugal pertaining to its African possessions."--Preface.